2020
DOI: 10.1002/stc.2482
|View full text |Cite
|
Sign up to set email alerts
|

Performance assessment of the KDamper as a seismic Absorption Base

Abstract: Summary The KDamper is a novel passive vibration absorption concept based essentially on the optimal combination of appropriate stiffness elements, one of which has a negative value. In this paper, the implementation of the KDamper as a seismic Absorption Base (KDAB) is considered. The performance of the KDAB is assessed in three characteristic test cases, namely, a rigid body and two flexible buildings with fundamental periods of 0.5 and 1.0 s, respectively. In all three cases, the structures are excited by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 40 publications
0
51
0
Order By: Relevance
“…In the second and third cases, the SBA's maximum inerter coefficient is bmax=1 (100%) and 2 (200%) respectively. The performance of the SBA-AF is compared with the previous optimal design of KDamper, as presented in [37]. For this reason, two sets of parameters of each concept, that present similar results, in terms of the structure's dynamic responses, are selected and compared in Table 1.…”
Section: Optimization Resultsmentioning
confidence: 99%
“…In the second and third cases, the SBA's maximum inerter coefficient is bmax=1 (100%) and 2 (200%) respectively. The performance of the SBA-AF is compared with the previous optimal design of KDamper, as presented in [37]. For this reason, two sets of parameters of each concept, that present similar results, in terms of the structure's dynamic responses, are selected and compared in Table 1.…”
Section: Optimization Resultsmentioning
confidence: 99%
“…The design of KDamper follows the procedure described in Kapasakalis et al [37], for optimal acceleration response, and is implemented as a stiff vibration absorber with a nominal frequency of 1 Hz. The Transfer Functions It is observed that the inerter manages to reduce the natural frequency f0, as in the case of the QZS oscillator, without having to reduce the stiffness of the system (Figure 2.B) or increase the seismic load ( Figure 2.A).…”
Section: Dynamic Properties and Inherent Constraints Of Existing Basementioning
confidence: 99%
“…According to previous work of KDamper [32][33][34][35][36][37], an additional mass of 5% is efficient. In an effort to make the device more realistic and easier to implement, mD is selected as 0.1% of the structure mass.…”
Section: Optimization Constraints and Limitations Based On Engineerinmentioning
confidence: 99%
See 1 more Smart Citation
“…The KDamper is essentially an extension of the traditional TMD, by introducing an appropriate negative stiffness (NS) element to the the oscillating mass of the TMD. The amplitude of the inertia force of the additional mass and the amplitude of the NS force are exactly in phase, due to the negative value of the implemented stiffness element [26,27]. Although the KDamper oscillator incorporates a NS element, it is designed to be statically and dynamically stable.…”
Section: Introductionmentioning
confidence: 99%